Protocol: methodology for chromatin immunoprecipitation (ChIP) in Chlamydomonas reinhardtii - Strenkert Daniela (Plant Methods, 2011)
Abstract We report on a detailed chromatin immunoprecipitation (ChIP) protocol for the unicellular green alga Chlamydomonas reinhardtii. The protocol is suitable for the analysis of nucleosome occupancy, histone modifications and transcription factor binding sites at the level of mononucleosomes for targeted and genome-wide studies. We describe the optimization of conditions for crosslinking, chromatin fragmentation and antibody titer determination and provide recommendations and an example for the normalization of ChIP results as determined by real-time PCR.